State, Development Strategies and the “Right” Ideas for Latin America - Seiler, Cristhian (Sociedad y Economía, 2021)
Over the past two decades, the persistence of peripheral features in the productive structure of Latin American countries brings into question to what extent neo-developmental thinking has enabled the development of a consistent model as an alternative to the neoliberal model. As an analytical strategy, this work introduces a range of ideas and axioms that guide the State’s actions in the field of development policies. This work is theoretical and asserts that state actions and strategies never occur in a vacuum, but rather, are performed in the context of ideas and statements about how to achieve development, which are hegemonic, specific, and historically constructed. It is concluded that neo-developmental actions by the State should not be considered institutional failures or anomalies, but rather, interventions that are guided by “right” ideas that contribute to reproducing peripheral features.